Pengaruh Kecukupan Modal, Fungsi Intermediasi, Efisiensi Operasional, dan Pembiayaan Bermasalah Terhadap Profitabilitas (Studi Pada Bank Syariah Periode Januari 2010 - Juli 2014) - Rifqul Ma'isyah; Imron Mawardi (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
The research aims to analyze the influence of Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Opperational Efficiency (BOPO), and Non Performing Financing (NPF) to Return On Assets (ROA) of Sharia Banking in the period from January 2010 to July 2014. The sample population of the research is the Industry of Sharia Banking. Samples were taken by purposive sampling, which is taken from the Sharia Banking Industry. The analysis technique used in this research is by multiple linier regression that aims to obtain a comprehensive picture of the relationship between variables. The results of this research shows that the CAR, BOPO, and NPF have a significant influence on ROA of Sharia Banking. Whereas FDR has no significant influence on ROA of Sharia Banking. The amount of the contribution of the four variables on ROA is 47,20% while the remaining 52,80% influenced by other factors that are not included in the analysis of this research. The results of this research are expected to be guidelines for Sharia Banking in increasing the profitability of Sharia Banking.